The Application of Management Accounting Techniques at Star Hotels in Denpasar City - Ni Made Adi Erawati; Komang Ayu Krisnadewi (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2018)
This study aims to identify management accounting techniques applied in the hotel industry in Denpasar, Bali. Besides, this study also aims to find out how useful the information generated by the technique for management in the decision-making process. The survey results distributed offline and online are processed and analyzed by using descriptive techniques. The study results show that management accounting techniques have been applied in hotels within certain limits. The most common application of management accounting techniques employed by hotels is the preparation of flexible operating budgets and the financial performance assessment as a benchmark of budget conformity. Despite the less application of other management accounting techniques, the company realizes that the benefits resulting from this management accounting information are very important. The company's inability to provide information from other management accounting techniques is mostly caused by the inability of human resources in using such techniques.